Patient engagement in multimorbidity: a systematic review of patient-reported outcome measures - Barello, Serena; Anderson, Gloria; Bosio, Caterina; Lane, Deirdre A.; Leo, Donato G.; Lobban, Trudie C. A.; Trevisan, Caterina; Graffigna, Guendalina (Frontiers in Psychology, 2024)
Background People with multimorbidity are increasingly engaged, enabled, and empowered to take responsibility for managing their health status. The purpose of the study was to systematically review and appraise the psychometric properties of tools measuring patient engagement in adults with multimorbidity and their applicability for use within engagement programs. Methods PubMed, Scopus, Web of Science, and PsycInfo were searched from inception to 1 July 2021. Gray literature was searched using EBSCO host-database “Open dissertation”. The reference lists of studies meeting the inclusion criteria were searched to identify additional eligible studies. The screening of the search results and the data extraction were performed independently by two reviewers. The methodological quality of the included studies was evaluated with the COSMIN checklist. Relevant data from all included articles were extracted and summarized in evidence synthesis tables. Results Twenty articles on eight tools were included. We included tools that measure all four dimensions of patient engagement (i.e., engagement, empowerment, activation, and participation). Their psychometric properties were analyzed separately. Most tools were developed in the last 10 years in Europe or the USA. The comparison of the estimated psychometric properties of the retrieved tools highlighted a significant lack of reliable patient engagement measures for people with multimorbidity. Available measures capture a diversity of constructs and have very limited evidence of psychometric properties that are vital for patient-reported measures, such as invariance, reliability, and responsiveness. Conclusion This review clarifies how patient engagement, as operationalized in measures purporting to capture this concept, overlaps with, and differs from other related constructs in adults with multimorbidity. The methodological quality of psychometric tools measuring patient engagement in adults with multimorbidity could be improved. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=259968, identifier CRD42021259968.